The impact of COVID-19 on the municipal Regulation System (SISREG) of Rio de Janeiro (RJ) (Research, Society and Development, 2024)
This study aimed to analyze the impact of the Covid-19 pandemic on the SISREG for consultations and exams in Rio de Janeiro (RJ), covering the period between 2020 and 2023. This is descriptive research with a qualitative approach. Documentary research was conducted, selecting documents to analyze the legal and regulatory aspects of the actions taken to normalize outpatient care. Data referring to the Management of Regulation were extracted from the Portal da Transparência do SISREG municipal. The results show that the Covid-19 pandemic impacted the SISREG queue, with a variation of reduction in 2021 and then growth in demand for care over the years. This variable pattern reflects the oscillations in the demand for vacancies, intensified by the effects of the pandemic. Despite an increase in requested and offered vacancies in 2023, waiting time continued to grow, raising questions about the effectiveness of health management interventions. Factors such as the suspension or reduction of outpatient services, the overload of the health system, and social distancing measures were identified as the main reasons for the prolongation of waiting times. Attempts to mitigate these times during the pandemic proved inadequate to address the challenges of the outpatient health system.